2017
DOI: 10.4014/jmb.1609.09004
|View full text |Cite
|
Sign up to set email alerts
|

Design, Characterization, and Antimicrobial Activity of a Novel Antimicrobial Peptide Derived from Bovine Lactophoricin

Abstract: Lactophoricin (LPcin), which is a part of proteose peptone isolated from bovine milk, is a cationic amphipathic α-helical antimicrobial peptide. Its truncated variants and mutated analogs were designed and their antimicrobial activities were evaluated by using various assays, like broth dilution methods and disk diffusion methods as well as hemolysis assay. Three analogs, LPcin-C8 (LPcin-YK1), LPcin-T2&6W (LPcin-YK2), and LPcin-T2&6W-C8 (LPcin-YK3), which showed better antibiotic activities than LPcin, were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…From the AFM imaging process, we suggest that SRP-2 could interact and disrupt bacterial membranes to perform its bactericidal activity. Previous studies have indicated that the interactions of an AMP with membrane components should result in conformational changes of the peptide 44 46 ; therefore, we applied CD spectroscopic measurements to examine the secondary structure changes of SRP-2 in membrane-mimicking environments. Moreover, 50% TFE has been used as one of the standard procedures for the induction of secondary structures of peptides in CD spectroscopy 47 50 .…”
Section: Resultsmentioning
confidence: 99%
“…From the AFM imaging process, we suggest that SRP-2 could interact and disrupt bacterial membranes to perform its bactericidal activity. Previous studies have indicated that the interactions of an AMP with membrane components should result in conformational changes of the peptide 44 46 ; therefore, we applied CD spectroscopic measurements to examine the secondary structure changes of SRP-2 in membrane-mimicking environments. Moreover, 50% TFE has been used as one of the standard procedures for the induction of secondary structures of peptides in CD spectroscopy 47 50 .…”
Section: Resultsmentioning
confidence: 99%
“…All the sequences had a disordered conformation in 1X PBS, while the original peptide and the four active derivatives (35409-1, -2, -4 and -13) had negative signals at~208 and 222 nm in SDS micelles (Figure 1), such signals being characteristic of an α-helix pattern [53]. AMPs' usual pattern consists of a disordered tendency in solution and the adoption of structural tendencies defined in a membrane or solvent environment simulating it, such as SDS [51,52,70]. A helix structure is the commonest one for AMPs, suggested here for all peptides acting against E. coli; for example, an α-helix structure is involved in 18.8% of the 41.5% of peptides having a known structure in the APD3 database (http://aps.unmc.edu/AP/statistic/statistic_structure.php).…”
Section: Discussionmentioning
confidence: 99%
“…As for the antibacterial activity, the interaction of AMPs with membrane components frequently correlates with antiviral effects, suggesting that the presence of a membrane could be one of the essential conditions in inducing the peptide conformation capable of inhibiting viral infection [57][58][59].…”
Section: Structural Characterization Of Rilk30 and Avp2mentioning
confidence: 99%